Factors associated with the uptake of newly introduced childhood vaccinations in Ethiopia: the cases of rotavirus and pneumococcal conjugate vaccines - Abrham Wondimu; Qi Cao; Jan C. Wilschut; Maarten J. Postma (BMC, 2019)
Abstract Background Childhood immunization programmes have made substantial contributions to lowering the burden of disease among children in developing countries, however a large proportion of children still remain unimmunized. This study aimed to explore the determinants of rotavirus vaccine (RVV) and pneumococcal conjugate vaccine (PCV) uptake in Ethiopia. Methods The 2016 Ethiopian demographic and health survey dataset was used in this analysis. A total of 2004 children aged 12-23 months were included in the analysis. A multivariable logistic regression model was employed to identify the determinants of uptake of the complete schedules of RVV (two doses) and PCV (three doses). Crude and adjusted odds ratios with 95% confidence intervals (CIs) were calculated. Results The uptakes of the complete schedules of RVV and PCV among children aged 12-23 months were 56 and 49.1%, respectively. The likelihood of immunization with the complete schedule of RVV was significantly lower among children from the relatively poor Afar region in Ethiopia (AOR 0.16; 95%-CI 0.04-0.61). Similarly, children living in not only the Afar region (AOR 0.10; 95%-CI 0.03-0.38), but also the Gambela region (AOR 0.25; 95%-CI 0.08-0.83), were less likely to be vaccinated with PCV. On the other hand, children from more wealthy households had higher odds of vaccination with RVV (AOR 1.69; 95%-CI 1.04-2.75). Also attending antenatal care (ANC) was found to be significantly associated with uptake of the complete schedule of RVV and PCV. Conclusions The uptake of RVV and PCV is suboptimal in Ethiopia. The uptake of the vaccines were found to be associated with region, ANC use and wealth status.